The Muslim world in cyberia: prospects for E-Governance and digital capacity building - Mohd Yusof, Danial (Palgrave Macmillan, Cham, 2019)
This chapter looks at the state of the Muslim world online and how digitalization, including the realm of online social networking, is contributing to new forms of social, cultural, economic, and political capital. It discusses how these types of capitals may contribute to new forms and dynamics of capacity building involving various stakeholders—governments, civil society organizations, think tanks, academia, and the citizen in a truly global context. The chapter explores the digital state of the Muslim world, sustainable strategies and policies for ICT development in Malaysia and Bahrain, a case study of the implications of ICT revolution and e-government on governance and development in Malaysia, and scenario planning and new visions of development for long-term policy formulation, intervention, and performance of the nation-state.